Levende vekselvirkning - Michelsen, William (Grundtvig-studier, 1989)
Living Interaction Viggo Mortensen: Theology and Science. Beyond Restriction and Expansion. Munksgaard, Copenhagen 1989. With an English Summary. Dissertation, University of Aarhus.God and Nature. Is a dialogue between theology and science feasible? Edit. Viggo Mortensen. Munksgaard, 1990.Reviewed by William Michelsen. In his World Chronicle from 1812 Grundtvig attacked the sciences, especially chemistry and the mathematical method, for leading away from religion and theology, and the attack caused a conflict between him and the physicist H.C. Ørsted in 1814-1815. Nevertheless, in 1829, Grundtvig left for England with a letter of recommendation from Ørsted, which opened all doors to him in Cambridge. – In a letter, written shortly before his departure, to the botanist and politician /. Fr. Schouw, who was angry about his pamphlet "The Rejoinder of the Church”, 1825, Grundtvig used the phrase ”living interaction” about the kind of relationship he wished to see between scientists and theologians, irrespective of the serious differences of opinion that might separate them individually. In his theological dissertation about the relationship today between theology and natural science Viggo Mortensen uses the same phrase, but in an extended sense so that in his use it covers the obligation for theology and science to accept each other’s way of thinking and in particular the obligation for theologians to embrace an evolutionist view as well as the world picture and view of man of modern science.Like Doctor of Divinity Rudolf Arendt in the book "God and Nature", which contains the contributions of the critics at the public defence of the dissertation and other comments on it, the present reviewer is of the opinion that there is a sharp distinction to be drawn between a justified and an unjustified extension of scientific principles to apply also to the theological view of the world and of man. When for example Grundtvig refused to acknowledge the Copernican world picture, it was because it clashed with the "Mosaic-Christian view of life" which Grundtvig asserted. On the other hand, the "Mosaic-Christian view", as Grundtvig interpreted it, did not conflict with the notion of man as a being undergoing a development. However, he places all the emphasis on the historical development of human culture that depends on the language. And the occurrences of "fall" in human life as well as in nature as a whole which science explains as physical phenomena, are interpreted theologically by Grundtvig as deviations from the destiny of man according to the Bible: to be like his Creator.Thus - much in the manner of Grundtvig - the present reviewer does not find it reasonable to accept the "evolutionary epic", in which Viggo Mortensen epitomizes a modern neo-Darwinistic view of the world and of man, but will accept the cautious dialogue which K.E. L.gstrup entered into in his latest works before his death.So the present reviewer finds it justified for theology to accept scientifically verifiable results. But he does not find it reasonable for theology to embrace a world picture or a concept of man that changes the view that man lives on a globe and in a world which he did not create, and that he imagines a creator and a creation as described in the Bible. - The task of science, as Grundtvig claimed, is to describe and explain man and the world he lives in. Theology is the science whose task it is to describe and explain the religious ideas about the world and about man, contained in Christianity. And these ideas are not of a scientific character. Thus there are intrinsic boundaries between the tasks of theology and science, as indeed human life is limited by time and space.